Evaluation of Chemical Composition, Functional Properties, and Sensory Attributes of Cabbage-Fortified Cassava Fufu - Roseline Nwabugo Attaugwu; Josephat Ikechukwu Anyadioha; Faith Ojo-Ago Ogbe (University of Sultan Ageng Tirtayasa, 2026)
Cassava fufu is a widely consumed staple food limited in protein, fiber, and micronutrients. This study investigated the potential of cabbage flour fortification to improve its nutritional quality and consumer appeal. Cassava-cabbage flour blends were formulated in ratios of 100:0 (control), 60:40 (C60Cb40), and 50:50 (C50Cb50). Standard analytical procedures were used to evaluate the samples for nutrient composition, functional properties, anti-nutrient/antioxidant and sensory attributes. Protein content increased from 1.36% (control) to 1.77% in C60Cb40, and crude fiber rose from 0.49% to 1.03% in C50Cb50. The control exhibited the highest water absorption capacity (70%), while C50Cb50 had the greatest swelling capacity (33.00 ml). Calcium and magnesium contents peaked in C60Cb40 at 301.95 mg/kg and 148.6 mg/kg, respectively. Vitamin B1 ranged from 0.24 to 0.81 mg/g, highest in C50Cb50, while flavonoids (1.05–4.38 mgQE/g) were most abundant in C60Cb40. Sensory scores ranged from 7.28 to 8.32, with C50Cb50 rated highest, indicating that fortification did not negatively impact acceptability. Cabbage fortification significantly (≤0.05) enhanced the nutritional and functional properties of cassava fufu without compromising sensory quality. This suggests its potential for improving the dietary value of cassava-based foods.